Maccera Tasi: Between Tradition and Social Prestige in Maritime Society - Yunus; Mukhlisin; Hendrayadi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study describes the relationship between the Maccera Tasi ritual and the economy of the Tokke Village community, using a phenomenological and ethnographic approach. Ritual values, use of historical space, community activities, beliefs, and historical values ​​affect the socio-economics of the community. Data were collected through interviews with village heads, religious leaders, traditional leaders, and the community. The results of the study show that the Maccera Tasi tradition has a sacred position and has a strong influence in society, especially when the fishing and harvest seasons arrive. This ritual increases the optimism and gratitude of fishermen, which has an impact on the catch. In addition, Maccera Tasi boosts the local economy by attracting tourists, thereby increasing community income. In addition, the relationship between religion and culture in the Maccera Tasi ritual is a complex and interesting area of ​​study, which offers the main findings and distinctions of this study that the Maccera Tasi Ritual has a dual function, namely as a cultural expression and religious practice. Culturally, this ritual strengthens social solidarity and the identity of the maritime community. Religiously, this ritual is a means to get closer to God and ask for protection from danger at sea